Crystal structure of NirF: insights into its role in heme d1 biosynthesis. (22nd April 2020) - Klünemann, Thomas; Nimtz, Manfred; Jänsch, Lothar; Layer, Gunhild; Blankenfeldt, Wulf
Abstract : Certain facultative anaerobes such as the opportunistic human pathogen Pseudomonas aeruginosa can respire on nitrate, a process generally known as denitrification. This enables denitrifying bacteria to survive in anoxic environments and contributes, for example, to the formation of biofilm, hence increasing difficulties in eradicating P. aeruginosa infections. A central step in denitrification is the reduction of nitrite to nitric oxide by nitrite reductase NirS, an enzyme that requires the unique cofactor heme d1 . While heme d1 biosynthesis is mostly understood, the role of the essential periplasmatic protein NirF in this pathway remains unclear. Here, we have determined crystal structures of NirF and its complex with dihydroheme d1, the last intermediate of heme d1 biosynthesis. We found that NirF forms a bottom‐to‐bottom β‐propeller homodimer and confirmed this by multi‐angle light and small‐angle X‐ray scattering. The N termini are adjacent to each other and project away from the core structure, which hints at simultaneous membrane anchoring via both N termini. Further, the complex with dihydroheme d1 allowed us to probe the importance of specific residues in the vicinity of the ligand binding site, revealing residues not required for binding or stability of NirF but essential for denitrification in experiments with complemented mutants of a Δ nirF strain of P. aeruginosa . Together, these data suggest that NirF possesses a yet unknown enzymatic activity and is not simply a binding protein of heme d1 derivatives. Database: Structural data are available in PDB database under the accession numbers 6TV2 and 6TV9 . Abstract : While heme d1 biosynthesis is mostly understood, the role of the essential periplasmatic protein NirF remains unclear. We determined the crystal structures of NirF and its complex with dihydroheme d1, the last intermediate of the pathway. Further, site‐directed mutagenesis revealed residues not required for ligand binding but essential for the in vivo function of the protein.